Teachers’ Difficulties on the Implementation of English as a Medium of Instruction for Young Learners - Cindi Oktavianti; Annisa Astrid; Eko Saputra (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The research was conducted to find out teachers’ difficulties on the implementation of English as a medium of instruction for young learners. This study used a qualitative method. The participants in this research were recruited from the teachers at SD Palm Kids Lubuklinggau who teach non English subjects by using English. Two teachers were selected to be the participants in this research based on the consideration.  In this study, the participants was selected using purposeful sampling technique. In collecting the data, the researcher used observation and interview to get several information about this research from the participants. The researcher used thematic analysis to analyzed the data about teachers’ difficulties on the implementation of using English as a medium of instruction for young learners. The result of this study showed that there were several difficulties that teachers’ faced on the use of English as a medium of instruction: 1) difficult in teaching non English subjects by using English; 2) difficult to select appropriate teaching methods; 3) difficult to handle students with lack of focus; and 4) difficult to handle students with lack of English profiency. The research findings implied that the teachers who teach by using English as a medium of instruction found it difficult in several ways. As a result, they have prepared suitable teaching strategies that are expected to be understood by students and create a more enjoyable learning experience in the classroom.